Configuration of Personal and Organizational Factors as Predictor of Turnover Intention in the Logistics Industry: Konfigurasi Faktor Pribadi dan Organisasi sebagai Prediktor Niat Pindah Kerja di Industri Logistik - Rahmadini Alifta Putri; Kukuh Harianto (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
This study examines the configuration of personal and organizational factors as predictors of turnover intention in the logistics industry, which faces significant challenges related to employee turnover. A Systematic Literature Review (SLR) method with the PRISMA approach was used to examine 20 scientific articles published between 2021 and 2025. The selected articles met the inclusion criteria: discussing turnover intention, conducted in the logistics industry, and published in reputable journals. The results indicate that personal factors such as mental health, work-life balance, and demographics, and organizational factors such as organizational culture, leadership style, compensation, and workload, are interrelated in influencing turnover intention. Poor mental health and excessive workload are the main causes of stress, while supportive leadership and fair compensation contribute to employee retention. The theoretical implications of these findings emphasize the importance of an integrative approach between personal and organizational factors. Practically, these results encourage the development of comprehensive HR policies, such as mental health programs and flexible work policies. This study also opens up opportunities to explore external factors such as the economic crisis and validate the findings through empirical studies.